Transmaterial 3 a catalog of materials that redefine our physical environment - Brownell, Blaine Erickson, 1970- (Princeton Architectural Press, 2010)
"Provides a broad synopsis of the state of technological advances in materials today, with a special emphasis on new developments in the field of biopolymers and various agriculturally derived products; biomimetic products, systems, and processes that seek to emulate natural examples, including low-embodied-energy and biochemically manufactured products; "grown" materials; nanoscale marvels; renewable energy technologies; "second-life" materials derived from repurposed waste; and responsive, interactive, and transformational digital interfaces that harness pervasive communication networks and are powered by low-energy illumination sources."--P. [4] of cover.